Feasibility and Merits of Performing Preclinical Imaging on Clinical Radiology and Nuclear Medicine Systems. (30th December 2013) - Bilgen, Mehmet
Abstract : Aim . Researchers have limited access to systems dedicated to imaging small laboratory animals. This paper aims to investigate the feasibility and merits of performing preclinical imaging on clinical systems. Materials and Methods . Scans were performed on rat and mouse models of diseases or injuries on four radiology systems, tomosynthesis, computed tomography (CT), positron emission tomography/computed tomography (PET-CT), and Magnetic Resonance Imaging (MRI), based on the availability at the author's institute. Results . Tomosysthesis delineated soft tissue anatomy and hard tissue structure with superb contrast and spatial resolution at minimal scan time and effort. CT allowed high resolution volumetric visualization of bones. Molecular imaging with PET was useful for detecting cancerous tissue in mouse but at the expense of poor resolution. MRI depicted abnormal or intervened tissue at quality and resolution sufficient for experimental studies. The paper discussed limitations of the clinical systems in preclinical imaging as well as challenges regarding the need of additional gadgets, modifications, or upgrades required for longitudinally scanning animals under anesthesia while monitoring their vital signs. Conclusion . Clinical imaging technologies can potentially make cost-effective and efficient contributions to preclinical efforts in obtaining anatomical, structural, and functional information from the underlying tissue while minimally compromising the data quality in certain situations.